2020
DOI: 10.1002/cia2.12127
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the clinical severity of atopic dermatitis with ocular comorbidities

Abstract: We compared the incidence of various ocular comorbidities and the clinical severity of AD using the Eczema Area and Severity Index (EASI) score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
2
1
Order By: Relevance
“…Head and neck score in AD patients presenting with lens opacity and retinal lesions is higher than that of AD patients without ocular complication; however, the difference was not statistically significant. 33 In this study, the total number of subjects was 70, and the prevalence of each ocular complication was different from our study. Therefore, the result can be different from our study due to statistical difference.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Head and neck score in AD patients presenting with lens opacity and retinal lesions is higher than that of AD patients without ocular complication; however, the difference was not statistically significant. 33 In this study, the total number of subjects was 70, and the prevalence of each ocular complication was different from our study. Therefore, the result can be different from our study due to statistical difference.…”
Section: Discussioncontrasting
confidence: 56%
“…However, in our study, no significant associations were found between intraocular complications such as cataract, retinal break, and retinal detachment and the total score for AD severity. In a study by Takafumi et al., 33 a significant association was observed between blepharitis and the whole body EASI score, but this association was not observed with the head and neck EASI score in Japanese patients. Head and neck score in AD patients presenting with lens opacity and retinal lesions is higher than that of AD patients without ocular complication; however, the difference was not statistically significant 33 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation